If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 60 = 2x + -12 Reorder the terms: 60 + 5x = 2x + -12 Reorder the terms: 60 + 5x = -12 + 2x Solving 60 + 5x = -12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 60 + 5x + -2x = -12 + 2x + -2x Combine like terms: 5x + -2x = 3x 60 + 3x = -12 + 2x + -2x Combine like terms: 2x + -2x = 0 60 + 3x = -12 + 0 60 + 3x = -12 Add '-60' to each side of the equation. 60 + -60 + 3x = -12 + -60 Combine like terms: 60 + -60 = 0 0 + 3x = -12 + -60 3x = -12 + -60 Combine like terms: -12 + -60 = -72 3x = -72 Divide each side by '3'. x = -24 Simplifying x = -24
| (5+a)3x=2 | | W/6=55/64 | | 44.96*20/100 | | 44.96x20/100 | | X+u=2 | | 12x+160=2x+100 | | 4x-3=89 | | x^2-3x-10=(x-2)*(x-5) | | -7+2b=-12+3b | | x^2-3x-10=(x+2)*(x+5) | | (y-40)+(x-20)+(x+10)=180 | | 4-5x=6x+2 | | 4-5x=5x+2 | | X+3-1=12 | | 2(x+5)=2(x+13) | | 3x(6x-7)=9 | | 2x+8=4-2x | | -27x+18y=54 | | 20x-120=5x+150 | | 13t+7-10t=2 | | 9tan(x/3) | | 3x+-2y+12=0 | | 5/6g-1/7g=9 | | P+p+35=635 | | 4(w-5)-7w= | | 2/5-7/20f=1/4 | | 20x+16y=6000 | | -2c+6=8 | | 110=v/5 | | x=-22/7 | | X^3-13x^2+15x-189=0 | | 7x+21=-1 |